Hard composite materials

The cBN sintered body with a specific bonding phase composition and Al2O3 dispersion provides enhanced fatigue and abrasive wear resistance, as well as resistance to impact and vibration damage, addressing the limitations of existing materials in rock excavation tools.

JP7649482B2Active Publication Date: 2025-03-21MITSUBISHI MATERIALS CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2022507213
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-13
Filing Date
2021-03-09
Publication Date
2025-03-21
Estimated Expiration
2041-03-09

AI Technical Summary

Technical Problem

Existing hard composite materials used in excavation tools, such as WC-based carbide alloys and cBN sintered bodies, lack sufficient fatigue wear resistance, abrasive wear resistance, and resistance to damage from impacts and vibrations when used for rock excavation.

Method used

A cBN sintered body with a bonding phase containing Ti2CN and TiAl3, where the peak intensity ratio of Ti2CN to TiAl3 is between 2.0 and 30.0, and the bonding phase is dispersed with Al2O3 particles of average size between 0.9 μm and 2.5 μm.

Benefits of technology

The cBN sintered body exhibits excellent fatigue wear resistance, abrasive wear resistance, and resistance to damage from impacts and vibrations, making it suitable for use as an excavation tool in rock excavation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007649482000006
    Figure 0007649482000006
  • Figure 0007649482000001
    Figure 0007649482000001
  • Figure 0007649482000002
    Figure 0007649482000002
Patent Text Reader

Abstract

A cubic boron nitride (cBN) sintered body comprising cBN particles and a binding phase, wherein: the binding phase contains Ti2CN and TiAl3; and, when the peak intensity of Ti2CN appearing at 2θ of 41.9 to 42.2° in XRD measurement is referred to as ITi2CN and the peak intensity of TiAl3 appearing at 2θ of 39.0 to 39.3° therein is referred to as ITiAl3, then the peak intensity ratio ITi2CN / ITiAl3 satisfies the requirement of being within the range of from 2.0 to 30.0.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hard composite material suitable for use in drilling tips of drilling tools. This application claims priority to Japanese Patent Application No. 2020-043693, filed on March 13, 2020. The entire contents of the Japanese Patent Application are incorporated herein by reference. [Background technology]

[0002] WC-based cemented carbide has high hardness and excellent toughness, and is used as a cutting tool and as a drilling tip for excavation tools. Cubic boron nitride sintered compacts (hereinafter sometimes referred to as cBN sintered compacts) are less hard than diamond, but have low reactivity with Fe-based and Ni-based materials, and are used as cutting tools and as drilling tips for excavation tools in Fe-based and Ni-based mines. Proposals have been made to improve the cutting and drilling performance of these WC-based cemented carbide and cBN sintered compacts.

[0003] For example, Patent Document 1 proposes a cemented carbide containing an iron-based metal, WC, and TiCN for use in the cutting edge of a deep drilling tool.

[0004] Also, for example, Patent Document 2 proposes a cBN sintered body for cutting tools or wear-resistant tools in which Ti2AlC is used as a binder phase forming substance, and the surface of this binder phase forming substance is activated to stimulate a reaction between the cBN and the binder phase, thereby forming a two-layer reaction layer on the surface of the cBN grains, consisting of a first layer containing Ti and boron and a second layer containing Al and boron over the entire surface of this first layer, thereby increasing the adhesion between the cBN and the binder phase and improving the strength, toughness, etc. of the sintered body.

[0005] Furthermore, for example, Patent Document 3 proposes a self-sintered polycrystalline cubic boron nitride compact having a first phase of cBN particles and a ceramic binder phase containing a titanium compound, in which the first phase accounts for more than 80 volume % of the boron compact, and further, the compact contains a binder phase having electrical conductivity or semi-conductivity by using Ti2AlC as a binder precursor, resulting in a high-cBN sintered body with excellent workability by electrical discharge machining. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Japanese Patent Application Publication No. 53-89809 [Patent Document 2] Japanese Patent Application Publication No. 5-310474 [Patent Document 3] JP 2013-537116 A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention has been made in consideration of the above circumstances and proposals, and has an object to provide a hard composite material that is excellent in fatigue wear resistance and abrasive wear resistance, and further has resistance to damage such as chipping due to impacts and vibrations used to break rocks, even when used as an excavation tool. [Means for solving the problem]

[0008] The cBN sintered body according to the embodiment of the present invention is It has cubic boron nitride particles and a binder phase. (However, 2 Co 21 B 6 phase not included) , The binder phase includes TiCN and TiAl; The peak intensity of TiCN appearing at 2θ = 41.9 to 42.2° in the XRD measurement is I Ti2CNThe peak intensity of TiAl3 appearing at 2θ = 39.0 to 39.3° is defined as I TiAl3 When The ratio of the peak intensities, I Ti2CN / I TiAl3 satisfies 2.0~30.0.

[0009] Moreover, the cBN sintered body according to the above embodiment may satisfy the following condition (1).

[0010] (1) The binder phase contains dispersed Al2O3, and the average particle size is 0.9 μm or more and 2.5 μm or less. Effect of the Invention

[0011] According to the above, a cBN sintered body is obtained which has excellent fatigue wear resistance and abrasive wear resistance, and further has resistance to damage such as chipping caused by impacts and vibrations for breaking rocks, even when used as an excavation tool. [Brief description of the drawings]

[0012] [Figure 1] 1 shows an XRD measurement chart of Example sintered body 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] As a result of studying the proposals described in the above-mentioned documents, the present inventors have come to the following realization.

[0014] The cemented carbide described in Patent Document 1 is intended for deep drilling, but since it is intended for drilling in a highly corrosive atmosphere, it has poor wear resistance when drilled deep into hard rocks. If it is used as the cutting edge of a drilling tool, it will wear out quickly and have a short lifespan.

[0015] The cBN sintered bodies shown in Patent Documents 2 and 3 are intended to be pressed against a workpiece of uniform composition, and therefore, when used as an excavation tool for excavating rocks, they do not have sufficient resistance to damage such as fatigue wear due to repeated impacts, abrasive wear due to micro-cutting action caused by hard components in the crushed rock getting between the tool cutting edge and the rock, and chipping due to impacts and vibrations used to break the rocks.

[0016] By the way, an excavation tool is a tool used to dig into the ground or rock. On the other hand, rocks underground are brittle materials with no uniform composition or strength. Therefore, unlike cutting processes that emphasize the ability to cut and remove, excavation tools must be able to withstand the shocks and vibrations used to break rocks, and also the rotation required to efficiently remove the broken rocks.

[0017] In other words, materials for drilling tools are required to be resistant to damage such as fatigue wear caused by repeated impacts, abrasive wear caused by the micro-cutting action that occurs when hard components of crushed rock get into the gap between the tool tip and the rock as it surrounds the drilling tool, and chipping caused by the impacts and vibrations used to break the rock.

[0018] Therefore, the present inventors conducted extensive research based on the above-mentioned findings, etc. As a result, they focused on cBN sintered compacts as hard composite materials, and discovered that when there is a predetermined relationship between the peak intensities of Ti2CN and TiAl3 constituting the binder phase during XRD measurement, it is possible to obtain cBN sintered compacts that are excellent in fatigue wear resistance and abrasive wear resistance, and further, when used as drilling tools, have resistance to damage such as chipping caused by impacts and vibrations used to break rocks.

[0019] The cBN sintered body according to the embodiment of the present invention will be described in more detail below. In the present specification and claims, when a numerical range is expressed as "A to B" (A and B are both numerical values), this is synonymous with "A or more and B or less", and the range includes an upper limit (B) and a lower limit (A). The upper limit and lower limit have the same unit. The numerical values ​​include a tolerance.

[0020] Cubic Boron Nitride (cBN) Particle Average Size: The average particle size of the cBN particles used in this embodiment is not particularly limited, but is preferably in the range of 0.5 to 30.0 μm.

[0021] The reason for this is that, in addition to the effect of enhancing fracture resistance by containing hard cBN particles in the sintered body, if the average particle size is 0.5 to 30.0 μm, not only can fracture and chipping originating from the uneven shape of the cutting edge caused by cBN particles falling off the surface of the tool during use as a drilling tool be suppressed, but also the propagation of cracks that develop from the interface between the cBN particles and the binder phase caused by stress applied to the cutting edge during use as a drilling tool, or cracks that develop as the cBN particles break apart, can be suppressed, thereby providing better fracture resistance.

[0022] Here, the average particle size of the cBN particles can be determined as follows. The cross section of the cBN sintered body is mirror-finished, and the mirror-finished surface is observed with a scanning electron microscope (hereinafter referred to as SEM) to obtain a secondary electron image. Next, the cBN grains in the obtained image are extracted by image processing, and the average grain size is calculated based on the maximum length of each grain obtained by image analysis.

[0023] When extracting the cBN particles from the image using image processing, the image was displayed in 256-level monochrome, with 0 being black and 255 being white, in order to clearly distinguish between the cBN particles and the binder phase. 、 Perform binarization processing.

[0024] In addition, it is desirable to select an area of ​​approximately 0.5 μm × 0.5 μm as the area for determining the pixel value of the cBN particle portion, and to use the average value determined from at least three different points within the same image area as the aforementioned pixel value of cBN.

[0025] After the binarization process, a process is performed to separate parts of the cBN grains that are thought to be in contact with each other, for example, watershed is used to separate the cBN grains that are thought to be in contact with each other.

[0026] The areas corresponding to the cBN particles in the image obtained after binarization (black areas) are subjected to particle analysis, and the maximum length of each particle obtained is taken as the diameter of each particle. In particle analysis to determine the maximum length, the larger of the two lengths obtained by calculating the Feret's diameter for one cBN particle is taken as the maximum length, and this value is taken as the diameter of each particle.

[0027] Then, assuming each particle is an ideal sphere with this diameter, the cumulative volume is calculated as the volume of each particle. Based on this cumulative volume, a graph is drawn with the vertical axis representing volume percentage (%) and the horizontal axis representing diameter (μm), and the diameter at which the volume percentage is 50% is taken as the average particle size of the cBN particles. This is done for the three observation areas, and the average value is taken as the average particle size of the cBN particles (μm).

[0028] When performing this particle analysis, the length per pixel (μm) is set using the scale value known in advance from the SEM. As the observation area used for image processing, a field of view of about 15 μm × 15 μm is desirable when the average particle size of the cBN particles is about 3 μm.

[0029] The content (volume %) of cBN particles in the cBN sintered body is not particularly limited. If the content of cBN particles is less than 65 volume %, the sintered body contains little hard material, and when used as a drilling tool, the chipping resistance may decrease. On the other hand, if it exceeds 93 volume %, voids that become the starting points of cracks may be generated in the sintered body, and the chipping resistance may decrease. Therefore, in order to further exert the effects of this embodiment, the content of cBN particles in the cBN sintered body is preferably in the range of 65 to 93 volume %.

[0030] The cBN particle content in a cBN sintered compact can be calculated as follows: the cross-sectional structure of the cBN sintered compact is observed by SEM, the cBN particle portion of the obtained secondary electron image is extracted by image processing, the area occupied by the cBN particles is calculated by image analysis, and the average value of the values ​​obtained by processing at least three images is taken as the cBN particle content (volume %). When the average particle size of the cBN particles is 3 μm, a viewing area of ​​about 15 μm × 15 μm is desirable as the observation area used for image processing.

[0031] Bonded phase: The ceramic binder phase of this embodiment can be produced using Ti2AlC powder, Ti3AlC2 powder, TiN powder, TiC powder, TiCN powder, and TiAl3 powder.

[0032] When the peak intensities of Ti2CN and TiAl3, which are components of the binder phase, are in a predetermined relationship during XRD measurement, that is, The peak intensity of TiCN appearing at 2θ = 41.9 to 42.2° in the XRD measurement is I Ti2CN The peak intensity of TiAl3 appearing at 2θ = 39.0 to 39.3° is defined as I TiAl3 Then, the peak intensity ratio, I Ti2CN / I TiAl3 When the average molecular weight is 2.0 to 30.0, the cBN sintered body has excellent wear resistance and abrasive wear resistance during rock excavation, and is highly resistant to damage such as chipping due to impact and vibration during rock excavation, which is preferable.

[0033] The reason is that I Ti2CN / I TiAl3 If I is less than 2.0, the cBN particles react with the excess TiAl3 in the sintered body to form coarse TiB2, which becomes the starting point of fracture during rock excavation. Ti2CN / I TiAl3 It is believed that if is greater than 30.0, the amount of TiAl3 in the sintered body will be small, resulting in a decrease in the adhesive strength between cBN and the binder phase and a decrease in the toughness of the sintered body.

[0034] Here, the TiCN peak intensity (I Ti2CN ) and the peak intensity of TiAl3 (I TiAl3 ) is confirmed by XRD measurement using a Cu tube. That is, the 111 diffraction line of cBN is set to 2θ=43.3, and based on this peak position (angle), the peak between 2θ=41.9 to 42.2° is set to Ti2CN, and the peak between 2θ=39.0 to 39.3° is set to TiAl3. After removing the background, a peak search is performed to confirm the intensity of each peak.

[0035] It is more preferable that Al2O3 is dispersed in the binder phase and that the average particle size of the Al2O3 be 0.9 μm or more and 2.5 μm or less.

[0036] The reason is that when the average grain size of Al2O3 is less than 0.9μm, the grain size of Ti2AlC or Ti3AlC2 required to generate Al2O3 is small, so the amount of Ti2CN or TiAl3 generated in the sintered body is small, and the toughness of the cBN sintered body may decrease.On the other hand, when the average grain size of Al2O3 exceeds 2.5μm, cracks due to fatigue accumulation originating from the Al2O3 particles in the binder phase are likely to occur, and the toughness of the cBN sintered body may decrease.

[0037] Here, the average particle size of Al2O3 is determined by mapping Al and O elements by SEM-EDX (Energy Dispersive X-ray Spectroscopy) and recognizing the overlapping portion of the two elements as Al2O3. The crystal grain size of each recognized particle is obtained by image analysis, and then the average grain size is calculated.

[0038] That is, the cross-sectional structure of the sintered body according to this embodiment is observed by SEM to obtain a secondary electron image, and a mapping image of the Al element and the O element at the same location is obtained by EDX. Then, the portion where the Al element and the O element overlap is binarized as Al2O3 by image processing and extracted.

[0039] When extracting each particle part from the image by image processing, in order to clearly distinguish each particle part, a gradation-processed image is used, which is displayed in monochrome with 256 gradations, with 0 being black and 255 being white.

[0040] After the binarization process, separation is performed using a process that separates areas where particles are thought to be in contact with each other, for example the watershed process mentioned above.

[0041] The areas corresponding to each particle in the image obtained after binarization (black areas) are subjected to particle analysis, and the maximum length of each particle obtained is set as the diameter of each particle, and the volume of each particle is calculated. The volume is calculated assuming that the particles are ideal spheres. When performing particle analysis, the length per pixel (μm) is set using the scale value known in advance from SEM.

[0042] Based on the cumulative volume of each particle, a graph is drawn with the vertical axis representing volume percentage (%) and the horizontal axis representing diameter (μm).The diameter when the volume percentage is 50% is taken as the average particle size of Al2O3 in the observed image, and the average value calculated from at least three images is taken as the average particle size (μm) of Al2O3 dispersed in the binder phase. The observation area used for image processing is preferably a viewing area of ​​about 12 μm×12 μm.

[0043] Bonded phase manufacturing method: The binder phase of the cBN sintered body of this embodiment can be produced, for example, as follows.

[0044] That is, prior to ultra-high pressure and high temperature sintering, Ti2AlC or Ti3AlC2 in the range of 1 to 500 μm is prepared. This is mixed with other raw materials and heat treated at 250°C to 900°C in a vacuum. This reduces the amount of water adsorbed on the surface of the raw materials without decomposing the coarse-grained Ti2AlC or Ti3AlC2 into TiO2 and Al2O3, and reduces the amount of Al2O3 generated in the sintered body after ultra-high pressure and high temperature sintering.

[0045] Here, by not crushing Ti2AlC or Ti3AlC2 finely, the inside of the coarse grains do not react with oxygen, and Ti2CN and TiAl3 are generated in the sintered body through ultra-high pressure sintering. TiAl3 reacts with cBN to generate TiB2 and AlN, which can increase the bonding strength between cBN and the binder phase. Furthermore, by leaving TiAl3, an alloy of Ti and Al, in the sintered body, the decrease in toughness caused by making the binder phase components coarse grains can be compensated for by TiAl3. This makes it possible to obtain a cBN sintered body that has excellent wear resistance and abrasive wear resistance during rock excavation, and is highly resistant to damage such as chipping due to impact and vibration during rock excavation. EXAMPLES

[0046] Next, examples will be described, but the present invention is not limited to the examples in any way.

[0047] This example was produced by the following steps (1) to (3).

[0048] (1) Preparation of raw powder As the hard raw material, cBN raw material with an average particle size of 0.5 to 35 μm was prepared, and as the raw material powder constituting the binder phase, Ti2AlC or Ti3AlC2 raw material was prepared. The Ti2AlC or Ti3AlC2 raw material had an average particle size of 50 μm. In addition, TiN powder, TiC powder, TiCN powder, and TiAl3 powder were separately prepared as raw material powders forming the binder phase. The average particle size of these separately prepared powders was 0.3 μm to 0.9 μm. The compounding composition of these raw materials is shown in Table 1.

[0049] (2)Mixture These raw material powders were mixed, and then filled into a container lined with cemented carbide together with cemented carbide balls and acetone, and after the container was covered, mixing was performed using a ball mill. The mixing time was 1 hour so as not to crush the raw material powder into small pieces. Although not performed in this example, it is more preferable to use an ultrasonic agitator to break down the agglomerates of the raw material powder while mixing.

[0050] (3) Molding and sintering Next, the obtained sintered body raw material powder was molded under a predetermined pressure to produce a molded body, which was then pre-heat-treated. After that, the molded body was charged into an ultra-high pressure sintering apparatus and sintered at a pressure of 5 GPa and a temperature of 1600°C to produce cBN sintered bodies 1 to 15 of the examples shown in Table 2 (hereinafter referred to as example sintered bodies).

[0051] The preliminary heat treatment was performed in a vacuum atmosphere with a pressure of 1 Pa or less, at 250°C to 900°C (referred to as "heat treatment temperature after mixing" in Table 2). The reason for this is as follows. If the temperature is less than 250°C, the adsorbed water does not dissociate sufficiently from the raw material surface, and Ti2AlC or Ti3AlC2 reacts with the water adsorbed on the raw material during ultra-high pressure and high temperature sintering, decomposing into TiO2 and Al2O3. As a result, less Ti2CN and TiAl3 remain in the binding phase of the sintered body after ultra-high pressure and high temperature sintering, reducing the toughness of the sintered body.

[0052] In addition, if the temperature is higher than 900℃, Ti2AlC or Ti3AlC2 reacts with oxygen in the adsorbed water during the preliminary heat treatment and decomposes into TiO2 and Al2O3. As a result, the amount of TiAl3 in the binder phase of the sintered body decreases, especially after ultra-high pressure and high temperature sintering, and the toughness of the sintered body decreases.

[0053] For comparison, a cBN sintered body of the comparative example was produced. The raw material powder was prepared by preparing a cBN raw material with an average particle size of 1.0 to 4.0 μm as a hard raw material, and a raw material powder containing Ti2AlC or Ti3AlC2 as a raw material powder constituting the binder phase. Here, the Ti2AlC and Ti3AlC2 raw materials had an average particle size of 50 μm. These were blended to obtain the compositions shown in Tables 1 and 3, and mixed by a ball mill under the same conditions as in the examples.

[0054] Thereafter, the mixture was molded at a prescribed pressure to produce a green compact, which was then pre-heat-treated at a prescribed temperature within the range of 100°C to 1200°C (referred to as "heat treatment temperature after mixing" in Table 4).Then, the mixture was loaded into an ultra-high pressure sintering apparatus and sintered at a pressure of 5 GPa and a temperature of 1600°C to produce the comparative cBN sintered compacts 1 to 5 shown in Table 4 (hereinafter referred to as comparative sintered compacts).

[0055] [Table 1]

[0056] [Table 2]

[0057] [Table 3]

[0058] [Table 4]

[0059] Here, the XRD measurement chart of the example sintered body 3 is shown in FIG. 1. As is clear from the figure, the sintered body has a peak intensity of Ti2CN appearing at 2θ=41.9 to 42.2° in the XRD measurement. Ti2CN The peak intensity of TiAl3 appearing at 2θ = 39.0 to 39.3° is defined as I TiAl3 When the ratio of the peak intensities is I Ti2CN / I TiAl3 It can be seen that satisfies 2.0 to 30.0.

[0060] Next, from the sintered bodies of the examples 1 to 15 and the sintered bodies of the comparison examples 1 to 5, tools having shapes conforming to ISO standard RNGN090300, Examples 1 to 15 and Comparative Examples 1 to 5, were produced, respectively, and these tools were attached to an NC lathe and subjected to the following wet cutting tests.

[0061] Cutting speed: 150m / min Depth of cut: 0.3mm Feed rate: 0.1mm / rev Material: Granite (Takine) Shape: Φ150mm x 200mmL

[0062] The amount of wear and condition of the cutting edge were checked when the cutting length (cutting distance) was 800 m. However, the cutting edge was observed every 100 m of cutting length to measure the presence or absence of chipping and the amount of wear, and if the amount of wear exceeded 2000 μm, the cutting test was stopped at that point. The results are shown in Table 5.

[0063] [Table 5]

[0064] As is clear from Table 5, all of the Examples have little wear and no chipping, and therefore have excellent abrasive wear resistance, and even when used as drilling tools, have resistance to damage such as chipping caused by impacts and vibrations used to break rocks. On the other hand, all of the Comparative Examples have chipping or large wear even with a short cutting length, and therefore have low abrasive wear resistance and are prone to chipping, making them difficult to use as drilling tools.

[0065] The above-disclosed embodiments are merely illustrative and not restrictive in all respects. The scope of the present invention is defined by the claims, not by the above-disclosed embodiments, and is intended to include the equivalent meanings of the claims and all modifications within the scope of the claims.

Claims

1. A cBN sintered body having cubic boron nitride particles and a binder phase, The binder phase contains Ti 2 CN and TiAl 3 (but does not include the W 2 Co 21 B 6 phase); Ti that appears at 2θ = 41.9 to 42.2° in XRD measurement 2 The CN peak intensity is I Ti2CN and TiAl appearing at 2θ=39.0 to 39.3° 3 The peak intensity of I TiAl3 When The ratio of the peak intensities, I Ti2CN / I TiAl3 A cBN sintered body characterized in that it satisfies the range of 2.0 to 30.

0.

2. The binder phase is Al 2 O 3 2. The cBN sintered body according to claim 1, characterized in that:

Citation Information

Patent Citations

  • Superhard alloy for bit

    JP1978089809A

  • Cutting tip made of cubic boron nitride group extra high pressure sintered material having high strength

    JP1992240006A

  • Cubic boron nitride-based ultrahigh pressure sintered material having high strength

    JP1993017233A

  • High-toughness boron nitride sintered compact with high-pressure phase

    JP1993310474A

  • Tool material and tool for cutting

    JP2004107154A